2019
DOI: 10.1093/mnras/stz023
|View full text |Cite
|
Sign up to set email alerts
|

Migrating super-Earths in low-viscosity discs: unveiling the roles of feedback, vortices, and laminar accretion flows

Abstract: We present the highest resolution study to date of super-Earths migrating in inviscid and low-viscosity discs, motivated by the connection to laminar, wind-driven models of protoplanetary discs. Our models unveil the critical role of vortices in determining the migration behaviour for partial gap-opening planets. Vortices form in pressure maxima at gap edges, and prevent the disc-feedback stopping of migration for intermediate planets in low-viscosity and inviscid discs, contrary to the concept of the 'inertia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 68 publications
(135 reference statements)
7
55
0
Order By: Relevance
“…These small-scale vortices, which are better resolved in the 1512×2250 simulation, thus tend to extend the runaway phase, and bring the planet closer to the grid's inner boundary. Similar results have been obtained by McNally et al (2019), who examined intermittent runaway migration in low-viscosity and inviscid disk models, and found that con-vergence in resolution was increasingly difficult to achieve, if achievable at all, upon decreasing viscosity. Although, in our simulations, stages of decelerated migration last shorter when increasing resolution, a pressure maximum does form when migration decelerates, but it is smoother, the density of dust trapped at this location is therefore smaller, and so is the intensity of the corresponding bright ring.…”
Section: Grid Resolutionsupporting
confidence: 82%
See 4 more Smart Citations
“…These small-scale vortices, which are better resolved in the 1512×2250 simulation, thus tend to extend the runaway phase, and bring the planet closer to the grid's inner boundary. Similar results have been obtained by McNally et al (2019), who examined intermittent runaway migration in low-viscosity and inviscid disk models, and found that con-vergence in resolution was increasingly difficult to achieve, if achievable at all, upon decreasing viscosity. Although, in our simulations, stages of decelerated migration last shorter when increasing resolution, a pressure maximum does form when migration decelerates, but it is smoother, the density of dust trapped at this location is therefore smaller, and so is the intensity of the corresponding bright ring.…”
Section: Grid Resolutionsupporting
confidence: 82%
“…As already stated in Section 3.1, Lin & Papaloizou (2010) and McNally et al (2019) have obtained a similar scenario of intermittent migration. Although in these mod-els gas vortices form at the edges of the planet gap due to the Rossby-Wave Instability, the intermittent episodes of runaway migration can also be accounted for by the time evolution of the inverse vortensity of the gas crossing the planet's orbit.…”
Section: Coorbital Vortensity Deficitsupporting
confidence: 61%
See 3 more Smart Citations